The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/1471301213485084
|View full text |Cite
|
Sign up to set email alerts
|

Enriching the care of patients with dementia in acute settings? The Dementia Champions Programme in Scotland

Abstract: Admission to hospital has been found to have a negative impact on people with dementia. The Scottish Dementia Champions programme was developed to prepare health and social service Dementia Champions working in acute settings as Change Agents. The programme was initially delivered to a cohort of 100 health professionals via blended learning, and comprised five study days, a half day spent in a local community setting, and e-learning. In order to complete the programme and graduate, participants were required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(80 citation statements)
references
References 20 publications
2
77
0
Order By: Relevance
“…This supports findings from previous studies (Banks et al, 2014, Elvish et al, 2013, Galvin et al, 2012 which have demonstrated similar results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This supports findings from previous studies (Banks et al, 2014, Elvish et al, 2013, Galvin et al, 2012 which have demonstrated similar results.…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, in a UK pre-post design study, Elvish et al (2013) found that in a sample of 71 general hospital staff who completed a 6-hour dementia training programme, knowledge about dementia, confidence in providing care to this group and beliefs about 'challenging behaviour', assessed using validated measures, significantly improved. Banks et al (2014) implemented a blended learning dementia champions programme comprised of 5 study days alongside a half day in a community care setting, with 100 staff working at an 'enhanced level' in acute settings. Participants were also required to undertake online activities in preparation for each study day, submit a reflective account of their half-day community observation and complete a written assignment.…”
Section: Background To the Studymentioning
confidence: 99%
“…Nurses from different studies in this review believed they lacked the authority or power to influence or implement changes in practice, which undermines programmes such as the Dementia Champions . Therefore, there is a need for a clear focus to develop organisation and clinical support for the nursing workforce, including nurses in both decision‐making processes and in the development of workplace environments and structures …”
Section: Discussionmentioning
confidence: 99%
“…New roles, such as Dementia Champions, are now being implemented in acute care environments to act as change agents, with some positive results . A number of papers were identified, which discussed the implementation of new roles; however, these were not included in this review, as they lacked outcome data of staff knowledge, skills or competencies, or outcomes for patients and their families .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation